Nanomaterial-mediated low-temperature photothermal therapy via heat shock protein inhibition - Xin, Yu; Sun, Zhuokai; Liu, Jie; Li, Wei; Wang, Meirong; Chu, Yongli; Sun, Zhihong; Deng, Guanjun (Frontiers in Bioengineering and Biotechnology, 2022)
With the continuous development of nanobiotechnology in recent years, combining photothermal materials with nanotechnology for tumor photothermal therapy has become a hot spot in the field of nanomedicine research. Although nanomaterial-mediated photothermal therapy is more specific and targeted than traditional treatment modalities, hyperthermia can also damage normal cells. Therefore, researchers have proposed the concept of low-temperature photothermal therapy, in which the expression of heat shock proteins is inhibited. In this paper, we review the research strategies proposed in recent years based on the inhibition of heat shock protein expression to achieve low-temperature photothermal therapy, introduce the synthesis, properties, and applications of these nanomaterials, and summarize the problems of nanomaterial-mediated low-temperature photothermal therapy at this stage and provide an outlook on future research directions.